PENGARUH KUALITAS AUDIT TERHADAP MANAJEMEN LABA DAN BIAYA MODAL EKUITAS - Jonata Agus Kurniawan; Daljono Daljono (Diponegoro Journal of Accounting, 2014)
The objective of this study is to examine the audit quality to earning managements and cost of equity capital. Audit quality can give the truth information to reduce agency cost. Earnings management is manager effort to manipulating financial statement for benefit their self. This behavior giving wrong information to financial statement user. Cost of equity capital is rate of return which required investor for invested capital to corporate. This study used manufacturing firm for sample during 2010-2011 by using purposive sampling method. The research use multiple regression for data analysis.The result showed that audit quality has significant effect to earnings management and cost of equity capital.